Godly republic : a centrist blueprint for America's faith-based future - DiIulio, John J., Jr., 1958- (Aaron Wildavsky forum for public policy ;, 2007)
Looks at the debate over whether as a nation America is Christian or secular and to what degree church-state separation is compelled by the Constitution. This book aims to offer a faith-inspired, and fact-based approach to enhancing America's civic future for one and all.